Crime and Punishment in Selected Modern African Novels (2014)
Crime, an act that contravenes societal values, and punishment, the penalty attracted by such act, are issues that abound in modern African novels. Previous studies on these novels have often examined the authors‟ thematic pre-occupations such as poor governance and political disillusionment, without adequate attention to the novelists‟ depiction of criminal acts and the consequent punishment. This study, therefore, examined the portrayal of these crimes and the punishment they attract in selected novels in order to portray the nature of crime and the corresponding punishment in different regions of Africa. Emile Durkheim‟s Deviance and Freud‟s Psychoanalytic theories were adopted due to their concern with the affirmation of cultural values and the motivation behind perpetration of crimes. Eight novels, representing four distinct regions of the continent were selected based on their thematic affinity and relevance to the study. They are: Ouologuem‟s Bound to Violence (BV), Achebe‟s Anthills of the Savannah (AS), Emecheta‟s The Joys of Motherhood (TJM), Ndibe‟s Arrows of Rain (AR) (West Africa), Salih‟s Season of Migration to the North (SMN), Mahfouz‟s The Thief and the Dogs (TTD) (North Africa), La Guma‟s A Walk in the Night (AWN) (South Africa) and Ngugi‟s The River Between (TRB) (East Africa). Four and two novels were respectively chosen from West and North Africa because they reveal more instances of crime and punishment. The data were subjected to literary analysis. Political, moral, gender, cultural, racial and religious crimes are perpetrated in the four regions of Africa. These crimes attract varying natural, judicial and extra-judicial punishments depending on the region and status of perpetrator. Political and moral crimes cut across the regions. Gender and moral crimes are common to North and West Africa, but while they are punished in West Africa, punishment is lopsided in North Africa due to their Islamic/patriarchal beliefs. In SMN, women are destroyed for challenging unequal marital choices. In TTD, judicial punishment is lopsidedly imposed; one of the three moral criminals is punished while others escape punishment. In West Africa, natural justice is meted to moral and cultural criminals in AR and TJM respectively. In AR, BV and AS while two political criminals escape punishment, judicial punishment is imposed on one. Racial crime is peculiar to South Africa where crimes are punished discriminatingly due to the segregated nature of the society. In AWN, crimes perpetrated by blacks attract judicial punishment while those committed by their white counterparts go unpunished. Religious crimes are peculiar to East Africa where the harsh Christianisation and land appropriation divide the community on religious affiliations. Supporters of western religion, attract extra judicial punishment by Kiama, a local group that upholds communal ways (TRB). In modern African novels, crimes identified and punished in Northern and Eastern Africa are those which relate to the dominant religion, but in the more westernised South and West African regions, political and moral crimes attract punishments due to their cultural, religious and educational similarities. Therefore, cultural, political and religious beliefs of particular regions of Africa determine the kind of punishments imposed on crimes